2005
DOI: 10.1021/om050096b
|View full text |Cite
|
Sign up to set email alerts
|

The Road to Early-Transition-Metal Phosphinimide Olefin Polymerization Catalysts

Abstract: This paper chronicles our work examining early-transition-metal systems incorporating phosphinimide ligands for use as olefin polymerization catalysts. Incorporation of these ancillary ligands affords unique deactivation pathways which are readily overcome by specific activation procedures and contrived ligand modification. In these ways, a new family of highly active olefin polymerization catalysts was successfully developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
124
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(126 citation statements)
references
References 70 publications
2
124
0
Order By: Relevance
“…A possible methyl group degradation pathway: In accord with organoaluminum-promoted (multiple) hydrogen abstraction reactions occurring in early transition metalmethyl complexes, [16,39] we propose the methyl group degradation scenario for LnA C H T U N G T R E N N U N G (AlMe 4 ) 3 -donor (Do) mixtures represented in Scheme 3.…”
Section: A C H T U N G T R E N N U N G (Ch 3 ) 30 ] (3 C)mentioning
confidence: 79%
See 1 more Smart Citation
“…A possible methyl group degradation pathway: In accord with organoaluminum-promoted (multiple) hydrogen abstraction reactions occurring in early transition metalmethyl complexes, [16,39] we propose the methyl group degradation scenario for LnA C H T U N G T R E N N U N G (AlMe 4 ) 3 -donor (Do) mixtures represented in Scheme 3.…”
Section: A C H T U N G T R E N N U N G (Ch 3 ) 30 ] (3 C)mentioning
confidence: 79%
“…La 4 Al 8 clusters and one La 5 Al 9 cluster produced multiple C À H bond activation featuring methylene, methine, or carbide C 1 functionalities. [16,17] The observation of methane and Me 3 AlA C H T U N G T R E N N U N G (PMe 3 ) in the NMR spectra, the irreversibility of the reaction, and the elemental analyses (Table 1) indicate that the few isolated crystals studied by X-ray diffraction must be similar in composition to the major product of the reaction.…”
Section: Reactivity Of [Lna C H T U N G T R E N N U N G (Alme 4 ) 3 ]mentioning
confidence: 99%
“…8) 61) . 1 H, 13 C as well as 15 N NMR (5 with 15 N enriched imine-N) studies have demonstrated that 5 exists as a mixture of isomers (the predominant isomer: B, Fig. 4).…”
Section: Well-defined Multimodal Pesmentioning
confidence: 98%
“…transition metal catalyzed coordination polymerization) in the copolymerization, it has thus been considered that design of the efficient transition metal complex catalysts that precisely control olefin polymerization should be the key for the success; the new catalysts described herein offer promising possibilities (See Reviews for cyclic olefin copolymers [4][5][6][7][8][9], See Reviews for metallocenes [11][12][13][14], See Reviews for linked half-titanocenes [15][16][17], See Reviews for nonbridged half-titanocenes [18][19][20], See Reviews for post-metallocenes [18][19][20][21][22][23][24], See Selected reviews for (co)polymerization of polar monomers [25][26][27], See Selected reviews for living polymerization [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]). …”
mentioning
confidence: 99%
“…Many researchers thus focused on designing the catalysts with ''constrained geometry type'' for the above reason (See Reviews for linked halftitanocenes [15][16][17]46]). Scheme 2.2, have been considered as promising candidates for the efficient catalysts (Reviews for cyclic olefin copolymers [9], See Reviews for nonbridged halftitanocenes [18][19][20][40][41][42], Our initial efforts in olefin polymerization and ethylene/a-olefin copolymerization, for example [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]81]), because these complex catalysts display unique characteristics especially for synthesis of new polymers (See Reviews for nonbridged half-titanocenes [19,20], Ethylene copolymerization with 2-methyl-1-pentene (disubstited a-olefin) [82,83], Copolymerization with aolefin containing bulky substituents [78][79][80], Copolymerization with norbornene [84][85][86][87], Copolymerization with cyclohexene, cyclopentene [88,89], Copolymerization with styrene with efficient...…”
mentioning
confidence: 99%